ANALYSIS OF MENTEN VILLAGE FUND MANAGEMENT, RAMBUTAN SUB-DISTRICT - Masayu Meysy Raudathul Jannah; farrel, farrel faadihilah; Enti, Wati Surtiningsih; Bayu aia , Bayu saputra; Embull, Siti Ambarwati; Almunawar, Muhammad Rafi Almunawar; Rafli, M.Rafli Adithio (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
This study aims to determine and describe the management of village funds in community empowerment in Menten Village, Rambutan District, Banyuasin Regency, namely in planning the implementation of administration, reporting, and accountability according to applicable procedures and rules. In addition, this study also aims to determine the inhibiting factors and supporting factors in managing village funds. This study used a qualitative descriptive method through a purposive sampling method. The data consists of information, namely the head of the village and development while the informants are the heads of the RT and the village community. Data collection techniques through observation, interviews, and books or journals. The results of the study show that Menten Village, Rambutan District, and Banyuasin Regency have implemented Village Fund management, although it is not yet optimal, it is still constrained by low human resources. This is known from the results of village development planning meetings which are monotonous every year. The reporting and accountability of the village government in managing village funds are carried out in accordance with applicable government regulations or provisions.